Application of selected speed development exercises for the national swimming team at Danang National Sports Training Center - Hung, T. M.; Hai, P. T.; Quan, P. Q. M. (Journal of Physical Education and Sport, 2025)
This study examined the selection and application of scientifically grounded speed development exercises to enhance short-distance swimming performance among elite athletes at Danang National Sports Training Center, Vietnam. Given that sprint performance is a decisive factor in competitive swimming, the study aimed to address existing performance limitations through a structured and context-appropriate training program. Twenty national-level swimmers (10 males, 10 females) were randomly assigned to either an experimental or control group. The experimental group participated in a six-month intervention that incorporated 29 exercises selected based on expert opinions (=80% approval), categorized into aerobic (n=12), anaerobic (n=9), and mixed (n=8) types. The control group continued with the standard of the national training program. Performance was assessed before and after the intervention using five tests: 25 m and 50 m freestyle, 200 m main stroke, 10×50 m (with 45-second rest), and 6×200 m (total time recorded). Results showed statistically significant improvements (p < 0.05) across all tests in the experimental group compared to the control group, validating the efficacy of the selected exercises. The study also identified four core principles for exercise selection: scientific justification, alignment with athlete capabilities, compatibility with existing facilities, and inclusion of techniques to maintain speed and initiate acceleration at critical points during races. The findings contribute practical insights for coaches and training institutions operating with insufficient resources, demonstrating that scientifically informed training models can yield substantial performance gains without reliance on advanced technology. This study also presents a replicable intervention framework adaptable to other national teams or training centers with similar limitations.